VvWRKY13 enhances ABA biosynthesis in Vitis vinifera - JIe Hao; Qian Ma; Lixia Hou; Fanggui Zhao; Liu Xin (Acta Societatis Botanicorum Poloniae, 2017)
Abscisic acid (ABA) plays critical roles in plant growth and development as well as in plants’ responses to abiotic stresses. We previously isolated VvWRKY13, a novel transcription factor, from Vitis vinifera (grapevine), and here we present evidence that VvWRKY13 may regulate ABA biosynthesis in plants. When VvWRKY13 was ectopically expressed in Arabidopsis, the transgenic lines showed delayed seed germination, smaller stomatal aperture size, and several other phenotypic changes, indicating elevated ABA levels in these plants. Sequence analysis of several genes that are involved in grapevine ABA synthetic pathway identified WRKY-specific binding elements (W-box or W-like box) in the promoter regions. Indeed, transient overexpression of VvWRKY13 in grapevine leaves significantly increased the transcript levels of ABA synthetic pathway genes. Taken together, we conclude that VvWRKY13 may promote ABA production by activating genes in the ABA synthetic pathway.